2017
DOI: 10.1021/acsami.7b11519
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature-Grown KNbO3 Thin Films and Their Application to Piezoelectric Nanogenerators and Self-Powered ReRAM Device

Abstract: Amorphous KNbO (KN) film containing KN nanocrystals was grown on TiN/SiO/Si substrate at 350 °C. This KN film showed a dielectric constant (ε) and a piezoelectric strain constant (d) of 43 and 80 pm/V at 10 V, respectively, owing to the existence of KN nanocrystals. Piezoelectric nanogenerators (PNGs) were fabricated using KN films grown on the TiN/polyimide/poly(ethylene terephthalate) substrates. The PNG fabricated with the KN film grown at 350 °C showed an open-circuit output voltage of 2.5 V and a short-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Therefore, it can be concluded that a crystalline phase was developed in the KN film deposited at 350 °C using PLD. According to a previous study, KN films that were grown by radio frequency (RF) sputtering on TiN electrodes at 350 °C exhibited an amorphous phase containing KN nanocrystals. , Therefore, it is considered that PLD is an effective method to produce a crystalline KN film at a lower temperature compared to RF sputtering and similar results have also been observed for other oxide films. , The crystalline KN memristor displayed a typical I – V curve of a ReRAM memristor with set and reset voltages of −1.2 and 1.5 V, respectively, as shown in Figure c. Currents in the high-resistance state (HRS) and low-resistance state (LRS) can be explained by the space-charge limited current (SCLC) mechanism and Ohmic conduction, respectively (Figure S1a).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, it can be concluded that a crystalline phase was developed in the KN film deposited at 350 °C using PLD. According to a previous study, KN films that were grown by radio frequency (RF) sputtering on TiN electrodes at 350 °C exhibited an amorphous phase containing KN nanocrystals. , Therefore, it is considered that PLD is an effective method to produce a crystalline KN film at a lower temperature compared to RF sputtering and similar results have also been observed for other oxide films. , The crystalline KN memristor displayed a typical I – V curve of a ReRAM memristor with set and reset voltages of −1.2 and 1.5 V, respectively, as shown in Figure c. Currents in the high-resistance state (HRS) and low-resistance state (LRS) can be explained by the space-charge limited current (SCLC) mechanism and Ohmic conduction, respectively (Figure S1a).…”
Section: Resultsmentioning
confidence: 68%
“…Moreover, the formation and rupture of oxygen vacancy filaments provide the switching mechanism of the crystalline KN memristor (Figure S1b). In addition, a forming process was needed to obtain an I – V curve for the amorphous KN film but the crystalline KN film did not need this forming process, revealing that the formation of oxygen vacancy filaments could be easier in the crystalline KN film than in the amorphous KN film.…”
Section: Resultsmentioning
confidence: 99%
“…[ 118 ] So far, many attempts had been made to fabricate PENG by employing various materials such as inorganic nanomaterials like BaTiO 3 , [ 119 ] ZnO, [ 120 ] and KNbO 3 . [ 121 ] Piezoelectric organic polymers like poly(vinylidene fluoride) (PVDF) [ 122 ] and poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE)) [ 123 ] are also widely utilized for fabricating flexible PENG for wearable applications. Nevertheless, most polymer‐based piezoelectric material exhibits bad piezoelectric performance, which hinders their wide applications for the fabrication of high‐performance PENGs.…”
Section: Flexible Devices Based On Natural Bio‐origin Materialsmentioning
confidence: 99%
“…Most of the interest was mainly focused on properties related to mechanics under the quantum confinement, leaving their electronic and magnetic properties with definitely similar fundamental scientific importance largely unexplored.Bulk KNbO3 (KNO) and KTaO3 (KTO) perovskites have been studied for over 70 years [17]. The former is famous as room-temperature lead-free ferroelectric material [18], while the latter is so-called incipient ferroelectric [19]. Some exotic properties based on them have been realized by doping, size, dimension or interface engineering, including the magnetic response in nanocrystalline KNO, two-dimensional electron gas…”
mentioning
confidence: 99%
“…Bulk KNbO3 (KNO) and KTaO3 (KTO) perovskites have been studied for over 70 years [17]. The former is famous as room-temperature lead-free ferroelectric material [18], while the latter is so-called incipient ferroelectric [19]. Some exotic properties based on them have been realized by doping, size, dimension or interface engineering, including the magnetic response in nanocrystalline KNO, two-dimensional electron gas…”
mentioning
confidence: 99%